Pengaruh Pembelajaran Berdiferensiasi Berbasis Proyek terhadap Keterampilan Berpikir Kreatif dan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila di SMPN 51 Surabaya - Tamara Augi Abadi; Listyaningsih L (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The low level of students' creative thinking skills has a direct impact on low learning outcomes, especially in Pancasila Education, which requires reflective and contextual thinking skills. Initial observations at SMPN 51 Surabaya showed that students tended to provide short, textual answers and were less able to develop and elaborate ideas in an original manner. This study aims to empirically test the effect of project-based differentiated learning on students' creative thinking skills and learning outcomes. This study used a quantitative approach with a quasi-experimental design, a nonequivalent control group design. The analysis results using the Mann–Whitney test showed an Asymp. Sig. (2-tailed) value of 0.007 (